PHARMACOLOGICAL SCREENING OF MUCUS PRODUCED BY THE PACAMÃ FISH, Lophiosilurus alexandri - CHARLIE-SILVA, I.; PEREZ, A. C.; DE MELO, N. F. S.; GOMES, J. M. M.; PORTELA, D.; SILVA, B.; FRACETO, L. F.; REZENDE-TEIXEIRA, P.; CORRÊA-JUNIOR, J. D.; CONCEIÇÃO, K.; PIEREZAN, F.; BELO, M. A. A.; et al. (Ars Veterinaria, 2021)
Recently, fish byproducts have been appraised as a source of structurally diverse bioactive compounds. In this context, fish mucus has revealed a myriad of pharmacological activities. This study describes a new bioactive molecule release system composed of protein nanoparticles from pacamã (Lophiosilurus alexandri) mucus, an endemic fish to the São Francisco River (Brazil). The process of obtaining and applying these nanoparticles, composed of proteins present in the pacamã mucus, as biocompatible carriers of bioactive molecules is also addressed herein. Therefore, the external mucus of the fish was collected, lyophilized and hydrated in deionized water containing the template molecule. After pH adjustment to 7.5, followed by sonication and centrifugation, the formed nanoparticles were collected in the supernatant. Additionally, the mucus and the particles were characterized, and pharmacological effects were evaluated regarding their antifungal, antibacterial, anticancer, anti or pro-inflammatory and antinociceptive proprieties. NP-Mucus did not exhibit antibacterial activity against Pseudomonas aeruginosa or Staphylococcus aureus. However, it showed potential effects against Candida albicans with a minimum inhibitory concentration (MIC) of 1 µg/mL, and significant pro-inflammatory role, reflected by cellular recruitment activity and healing effects. Therefore, future studies are now needed in order to identify specific compounds in NP-mucus responsible for the observed effects in order to provide new pharmacological and therapeutic strategies.